Prevalência de afecções orais e fatores de risco para a doença periodontal em cães - Ha, Juliana Dalarossa Amatuzzi Von (2013)
The purpose of this study was to appraise the prevalence of oral diseases and the risk factors for periodontal disease in dogs. A total of 126 dogs was examined without taking into consideration their specific breed, gender, age or weight, of which total 75 (59,52%) were from a kennel held by a university located in the countryside of the State of São Paulo and 51 (40,47%) belonged to private owners whose dogs were treated by the Small Animal Surgical Clinic. The data gathered during the physical examination were transferred to a specific form (dental chart). The owner or person in charge of each dog was requested to answer a questionnaire containing questions related to the medical and dental records of their dogs, as well as any habits of gnawing on natural or artificial bones or hard objects, and the type of feed used. Any extraoral alteration was examined, such as asymmetry of head, lips, submandibular lymph glands, presence or absence of fistulas and/or infraorbital increase. The intraoral examination was carried out next, which encompassed mucosa, palate, and alterations of teeth considering the presence or absence of gingivitis (degrees I, II, III), dental calculus (degrees I, II, III), exposition of a furcation (degrees I, II, III), dental mobility (degrees I, II, III), gingival retraction (mm), periodontal pocket (mm), tooth wear, dental fractures with or without pulpar exposure, gyroversion, dental crowding, enamel hypoplasia, gingival hyperplasia, persistence of decidual teeth, malocclusion, tooth absence, supernumerary teeth, bleeding on probing, conventional root canal treatment, lip fold dermatitis, oral papillomatosis, oronasal communication and periodontal disease (degrees I, II, III, IV). There was no significant relevance in relation to weight, type of feed and presence of periodontal disease, but the clinical importance of that relation is well known. The variables gender, origin of the animals (private owner or kennel), habit of gnawing on natural or artificial bones, type of occlusion, dental crowding, persistence of decidual teeth, supernumerary teeth and gyroversion did not reach statistical relevance when associated with periodontal disease. The conclusion reached was that there was a high prevalence of periodontal disease (80,95%) in the dogs examined. The disease most commonly found was dental calculus, followed by gingivitis and periodontal disease degree I. The degree of periodontal disease was correlated to the degree of dental mobility, gingivitis, dental calculus, depth of the periodontal pocket and gingival retraction.